A "Two‐incision" Approach for En Bloc Resection of Periacetabular Tumors with Illustrations from a Cadaver. Issue 1 (February 2014) - Guo, Chang‐an; Yan, Zuo‐qin
<x xml:space="preserve">Abstract</x> A "two‐incision" approach for en bloc resection of periacetabular tumors and prosthesis reconstruction is described. The first incision begins in the middle of the iliac crest, continues over the inguinal ligament, extends to the symphysis pubis and then turns down to ischial tuberosity. The muscles attached to the iliac crest are only separated from its internal side. All the attachments of the abductor muscles to the iliac crest are left intact. The second incision runs from the sacroiliac joint to the greater trochanter and is curved in shape, providing external exposure of the sciatic notch and ischial tuberosity. Communication between the two approaches is possible inside and outside under the abductor muscles or through the sciatic notch. En bloc resection of the tumor is performed by cutting the pubic symphysis and iliac as planned preoperatively. The iliac osteotomy is performed by using a Gigli saw that has been led through the sciatic notch and under the abductor muscles. This "two‐incision" approach not only provides enough exposure to perform en bloc resection of periacetabular tumors, but also protects the continuity of the abductor muscles between the pelvis and greater trochanter, thus preventing prosthesis dislocation.